Variations of transesophageal echocardiography practices in India: A survey by Indian College of Cardiac Anaesthesia - Borde, Deepak; George, Antony; Joshi, Shreedhar; Nair, Suresh; Koshy, Thomas; Gandhe, Uday; Chakravarthy, Murali (Annals of cardiac anaesthesia, 2016)
Context: Use of perioperative transesophageal echocardiography (TEE) has expanded in India. Despite attempts to standardize the practice of TEE in cardiac surgical procedures, variation in practice and application exists. This is the first online survey by Indian College of Cardiac Anaesthesia, research and academic wing of the Indian Association of Cardiovascular Thoracic Anaesthesiologists (IACTA). Aims: We hypothesized that variations in practice of intraoperative TEE exist among centers and this survey aimed at analyzing them. Settings and Design: This is an online survey conducted among members of the IACTA. Subjects and Methods: All members of IACTA were contacted using online questionnaire fielded using SurveyMonkey™ software. There were 21 questions over four pages evaluating infrastructure, documentation of TEE, experience and accreditation of anesthesiologist performing TEE, and finally impact of TEE on clinical practice. Questions were also asked about national TEE workshop conducted by the IACTA, and suggestions were invited by members on overseas training. Results: Response rate was 29.7% (382/1222). 53.9% were from high-volume centers (>500 cases annually). TEE machine/probe was available to 75.9% of the respondents and those in high-volume centers had easier (86.9%) access. There was poor documentation of preoperative consent (23.3%) as well as TEE findings (66%). Only 18.2% of responders were board qualified. Almost 90% of the responders felt surgeons respected their TEE diagnosis. Around half of the responders felt that new intraoperative findings by TEE were considered in decision-making in most of the cases and 70% of the responders reported that surgical plan was altered based on TEE finding more than 10 times in the last year. Despite this, only 5% of the responders in this survey were monetarily awarded for performing impactful skill of TEE. Majority (57%) felt that there is no need for overseas training for Indian cardiac anesthesiologists. Conclusions: In this survey of members of the IACTA, use of TEE has increased substantially, but still a lot of variations in practice patterns exist in India. There is urgent need for improving TEE certification and upgrade documentation standards, motivate use of TTE across all centers, promote awareness and usefulness of TEE use among surgical fraternity, monitor impact of TEE, and support separate remuneration policy in India.